Special Section: IT-Enabled Social and Economic Transitions - CLEMONS, Eric K. (Institutional Knowledge at Singapore Management University, 2014)
The economic and strategic issues surrounding information technology have become relevant to society at large. They tend to have a wider reach, often touching the very fabric of society. What used to be appropriately delimited as “e-commerce” or “e-business” is now merely “commerce” or “business.” Information technology is breaking out of its traditional confines, as its pervasive impact is being felt at a societal level. The articles included in this Special Section reflect this broadened perspective, both empirically and theoretically, by addressing the diffusion of information technology in healthcare, a legacy domain at the core of society, and by examining the inner workings of an emerging sharing economy, which is set to supersede the traditional ownership economy.